The Authority of Notary as Class II Auction Official in Providing Legal Counseling on The Auction Minutes Deed They Create - Budiman, Seno Aziz; Ramadhan, Muhammad Willy; Tarigan, Notora; Maskanah, Ummi (Manunggal Halim Jaya, 2025)
This study aims to analyze the authority of a notary as a class II auction official in providing legal counseling related to the auction minutes deed they create. This research focuses on understanding the notary's role in ensuring that the parties involved in the auction gain a clear legal understanding of their rights and obligations and provide accurate explanations regarding the auction process as reflected in the auction minutes deed. The study's findings show that the notary's authority as a class II auction official in providing legal counseling is crucial to ensuring that the auction process proceeds by the applicable legal provisions. The notary plays a key role in explaining the legality of the auction minutes deed, which can influence the decisions of the auction participants. However, challenges in implementing this authority were found, such as the limited legal understanding of the parties involved and the lack of coordination between the notary and the auction institution.